1963
DOI: 10.1016/0022-3115(63)90174-0
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy of uranium

Abstract: -. . . *The information contained i n t h i s a r t i c l e was developed d u r i n g t h ecourse of work under c o n t r a c t AT( 07-2) -1 w i t h t h e U. S. Atomic 0 Energy Commission. / d /

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…All potentials representing stable polishing were ultimately limited in current density at 20-25 mA/cm 2 at 210s. 30 mA/cm 2 has been reported as optimal polishing conditions using a similar solution [15].…”
Section: Polishing Potentialsmentioning
confidence: 90%
“…All potentials representing stable polishing were ultimately limited in current density at 20-25 mA/cm 2 at 210s. 30 mA/cm 2 has been reported as optimal polishing conditions using a similar solution [15].…”
Section: Polishing Potentialsmentioning
confidence: 90%
“…at 500 kv. The maximum magnification is 100,000X and the resolution better than 20 A. The maximum camera length of selected area diffraction is about 2 meters.…”
Section: Instrumentsmentioning
confidence: 99%
“…Angerman (20) prepared thin uranium foils for transmission electron microscopy by the anodic treatment of thin U specimens in a solution of alcohol, ethylene glycol, and H3P04 at room temperature and a current density of 30 ma./sq. cm.…”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several references to sample preparation of uranium for TEM analysis appear in the literature (Ammons, 1976;Angerman, 1963Angerman, , 1965Davies, 1968, Douglass, 1965Ferguson, 1972;Greulich, 1969;Kloepper, 1966;Makin, 1960;Mastel et al, 1965;Porter & Rickman, 1968;Romig, 1981;Romig et al, 1982), but the studies in this laboratory found the published procedures to be inadequate. The procedures were either useful for only a limited number of alloys or produced samples with oxide layers too thick for analytical electron microscopy.…”
Section: Introductionmentioning
confidence: 99%